Penerapan Algoritma EA-SHORT pada Protokol Routing AOMDV untuk Menemukan Rute yang Handal Berbasis Energi di Jaringan MANET - B. Nurwahyu Hairani; Andy Hidayat Jatmika; Fitri Bimantoro (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2021)
Mobile Ad Hoc Network (MANET) is a stand-alone wireless network, consisting of several nodes that can move in all directions freely. The routing protocol used as the object of this study is Ad Hoc On-Demand Multipath Distance Vector (AOMDV). This research carries out an energy calculation process at a node that can be used as a new energy-based route by utilizing topology changes. Energy efficiency in the routing protocol can be done using the Energy-Aware SHORT (Self Healing and Optimizing Routing Techniques) method. The main purpose of the Energy-Aware SHORT (EA-SHORT) algorithm is to save energy on MANET, by extending the life of nodes and networks by routing packets through nodes that have enough remaining power and avoiding nodes that have low power. AOMDV performance will be compared with AOMDV which has been modified with EA-SHORT measured from the specified parameter values. Analysis results show that the application of the EA-SHORT algorithm in the efficiency of route search succeeded in improving performance. The results of throughput on EA-AOMDV increased by 13.904% for an area of ​​500x500 m2 and 13.905% at 1000x1000 m2. The packet delivery ratio increased by 0.91% and 2.273%. Average end-to-end delay decreased by 20.482% and 18.734%.